Protective effects of miR-24-2-5p in early stages of breast cancer bone metastasis - Margherita Puppo; Martine Croset; Davide Ceresa; Manoj Kumar Valluru; Victor Gabriel Canuas Landero; Monserrat Hernandez Guadarrama; Michele Iuliani; Francesco Pantano; Penelope Dawn Ottewell; Philippe Clézardin (Breast Cancer Research)
Abstract Background Bone is the most frequent site of metastasis for breast cancer (BC). Metastatic BC cells interact with bone cells, including osteoclasts and osteoblasts, creating a cancer niche where they seed and proliferate. MicroRNAs (miRNAs) are regulators of breast-to-bone metastasis progression. MiR-24-2-5p has previously been shown to have roles in both breast cancer progression and inhibition of osteogenic differentiation. However, a direct link between miR-24-2-5p activity and the onset of bone metastasis remains ill-defined. Methods Analysis of the expression of miR-24 forms (miR-24-2-5p, miR-24-3p, miR-24-1-5p) in the serum from early-stage BC patients at baseline (time of surgery) was conducted. MiR-24-2-5p overexpression in BC cells (NW1, a luc2-positive subpopulation of MDA-MB-231, and MCF7) was obtained by miRNA mimic transfection or lentivirus transduction. MiR-24-2-5p downregulation in BC cells (ZR-75-1, T-47D, SK-BR-3) was obtained by miRNA inhibitor transfection. Cell proliferation, migration and/or invasion assays were performed to assess BC cell functions after modulation of miR-24-2-5p expression. An animal model was used to assess the effect of miR-24-2-5p overexpression on early BC metastasis formation, as judged by bioluminescence imaging, and on bone remodelling, following measurement of circulating bone resorption (CTX-I) and bone formation (P1NP) markers. The effect of conditioned medium from miR-24-2-5p-overexpressing BC cells on human and murine osteoclast differentiation was investigated. Endogenous miR-24-2-5p expression levels were also quantified during murine osteoclast differentiation. RNA-sequencing (RNA-seq) analysis of BC cells was performed to evaluate transcriptomic changes associated with miR-24-2-5p overexpression. Selected modulated transcripts upon miR-24-2-5p overexpression were further validated by real-time qPCR. Results Low expression levels of miR-24-2-5p, but not other miR-24 forms (miR-24-3p, miR-24-1-5p), in the serum from early-stage BC patients were associated with a high risk to develop future (bone) metastases. MiR-24-2-5p was also present in small extracellular vesicles secreted from BC cells. Forced expression of miR-24-2-5p in BC cells (NW1, MCF7) reduced their malignant traits (migration, invasion, and proliferation) in vitro. Furthermore, miR-24-2-5p overexpression in NW1 cells reduced metastasis, particularly in bone, and decreased bone turnover in vivo. RNA-seq and real-time qPCR analyses of NW1 and MCF7 cells overexpressing miR-24-2-5p showed the downregulation of common transcripts (CNNM4, DCTD, FMR1, PIGS, HLA-A, ICK, SH3BGRL2, WDFY, TRAF9B, IL6ST, PEX10, TRIM59). The conditioned medium from BC cells overexpressing miR-24-2-5p decreased human and murine osteoclast differentiation in vitro. Additionally, endogenous miR-24-2-5p expression levels in murine bone marrow-derived monocytes decreased during their differentiation into osteoclasts, further suggesting an inhibitory role for miR-24-2-5p during osteoclastogenesis. Conclusion MiR-24-2-5p exerts multiple protective roles in the early steps of BC bone metastasis by reducing malignant BC cell traits and tumour cell dissemination in bone, as well as by reducing the differentiation of precursors into mature osteoclasts.